The Causal Relationship between Interns' Knowledge and Self-Efficacy and Their Value in Predicting the Interns' Communication Behavior with Patients - Saeideh Ghaffarifar; Fazlollah Ghofranipour; Fazlollah Ahmadi; Manouchehr Khoshbaten; Chris Sallis (Shiraz University of Medical Sciences, 2015)
Abstract Background: After many years of teaching, both the efficiency and efficacy of communication skills programs are under question because patients' dissatisfaction with doctors' communication behavior is at the top of the complaint lists. It is assumed that finding the specific role of different determinants of doctors' communication behavior, instructional designers can plan more effective training programs. This study aims to explore the predictive value of interns' knowledge and self-efficacy in building effective relationship with patients and determine the causal relationship between interns' knowledge and self-efficacy about effective doctor-patient relationship. Methods: In this cross-sectional study, PRECEDE model was applied and the analyzed content from semistructured interviews with 7 interns and 14 faculty members was combined with the items from literature review. All the emerged items were categorized under eight constructs of social cognitive theory. The validity and reliability of the items of the research questionnaire were examined by 40 interns and an expert panel of 14 faculty members. The questionnaires were completed by 203 medical interns and confirmatory factor analysis (CFA) was done on the items. The data were analyzed by SPSS.21 and LISREL 8.80. Results: CFA indicated a good fit to the data. Knowledge and self-efficacy, together, explained 23 percent of the variance in interns' communicative behavior. 53 percent of the changes in interns' selfefficacy were attributed to the changes in interns' knowledge. Conclusion: Improving the interns' shared vision can increase the quality of their knowledge and instructional designs based on learning facts, and gaining insights about effective doctor-patient relationship can increase the interns' self-efficacy and consequently improve the interns' communication skills.